PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, PROFITABILITAS,DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN STUDI PADA EMITEN SEKTOR MANUFAKTUR DI BEI - Neneng Lasmita Susanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
This study examines the effect of capital structure, growth, and profitability on dividend policy and value of thefirm's manufacturing sector issuers listed on the Stock Exchange in the period 2009-2013. Samples were takenthrough purposive sampling a total of 18 issuers. The results of this study found: (1) significant negative effect ofcapital structure on dividend policy, (2) the growth of the company significant negative effect on dividend policy, (3)the profitability of a significant positive effect on dividend policy, (4) capital structure significant negative effect onvalue of the firm, (5) the firm growth is not a significant positive effect on firm value, (6) the profitability of asignificant positive effect on firm value, and (7) the dividend policy of a significant positive effect on firm value. Theresults of this study also found the most dominant in the capital structure affects the dividend policy and value of thefirm